2020
DOI: 10.3390/ijerph17103490
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Muscular Skeletal Disorders among Qualified Dental Assistants

Abstract: The occupation of dental assistants (DAs) involves many health risks of the musculoskeletal system due to static and prolonged work, which can lead to musculoskeletal disorders (MSDs). The aim of the study was to investigate the prevalence of MSDs in DAs in Germany. Methods: For this purpose, an online questionnaire analyzed 406 (401 female participants and 5 male participants, 401w/5m) DAs. It was based on the Nordic Questionnaire (lifetime, 12-month, and seven-day MSDs’ prevalence separated into neck, should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 47 publications
3
39
0
6
Order By: Relevance
“…26 The prevalence rates in comparable studies with a moderate or high quality from Western countries are over 80%. [27][28][29][30] Our results are in line with recent findings of Ohlendorf et al 31 They documented overall prevalence of MSD for the last 12 months from 92%. Most affected body regions included neck and shoulders (70.9% respectively 55.6%).…”
Section: Discussionsupporting
confidence: 93%
“…26 The prevalence rates in comparable studies with a moderate or high quality from Western countries are over 80%. [27][28][29][30] Our results are in line with recent findings of Ohlendorf et al 31 They documented overall prevalence of MSD for the last 12 months from 92%. Most affected body regions included neck and shoulders (70.9% respectively 55.6%).…”
Section: Discussionsupporting
confidence: 93%
“…Among dentists in Saudi Arabia, lower back, neck, and shoulders were also the most prevalent body sites for MSDs [ 25 , 47 ]. These findings match the numbers reported among German [ 45 ], Thai [ 29 ], and Sudanese ADP populations [ 46 ]. However, in a study by Ohlendorf et al [ 45 ], dental assistants reported a higher prevalence of MSDs of the neck (85%) and shoulders (70%) compared to our results, but similar percentages for the lower back (60%) and upper back (48%).…”
Section: Discussionsupporting
confidence: 91%
“…In total, 93% of the sample reported MSD symptoms of at least one body site during the past 12 months. Other studies showed that the 12-month prevalence of MSD symptoms of any body site for ADPs ranged between 44.9% and 97.5% [ 28 , 29 , 45 , 46 ]. Very few studies have assessed MSDs among ADPs in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Such risk factors include instrument vibration, poor lighting conditions, poor positioning of the dental professionals when working on the patients or poor positioning of the patients [2][3][4]. The impact on the musculoskeletal system in dentistry is high, the upper extremity being especially very vulnerable [4][5][6][7][8][9]. Lietz et al [10] reviewed the prevalence of muscular-skeletal disorders (MSDs) among dental professionals in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, after the shoulders, the hands in the upper extremities are the next most frequently affected body part [ 10 ]. The 12-month prevalence of MSDs in the hand varies between 25.0% and 49.7% [ 4 , 9 , 11 13 , 18 20 ]. Other international studies report hand complaints ranging from 8.4% to 66.7% [ 8 , 14 , 15 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%